Sulfur enriched cobalt-based layered double hydroxides for oxygen evolution reactions - Ullah, S. (Elsevier Ltd, 2021)
Sulfur and zinc substituted Co(OH)2 is synthesized by a simple co-precipitation one-step method followed by solvothermal treatment for oxygen evolution reaction. The high-resolution X-ray photoelectron spectroscopy (XPS) and high-resolution transmission electron microscopy (HRTEM) demonstrates that the Zn and S substitution significantly stabilizes the layered structure and causes an increase in the electron density around the Co center. The role of both cation and anion substitution is evaluated to enhance the oxygen evolution reactions. This enhanced activity is due to the in-situ oxidation of divalent Co into trivalent Co, and partially due to the stabilization of the layered structure, as highlighted by PXRD and TEM analysis, the gap between the layers is slightly reduced from 7.8 Ã to 7.5 Ã , for SâZnâCo(OH)2. The in-situ conversion of Co2+ to Co3+ during electrocatalysis improved the OER electrocatalysis. The structural and physical characterizations are performed via XRD, EDX, SEM, TEM, XPS, AFM and BET. Â© 2021 Hydrogen Energy Publications LLC